Ciliary IFT88 Protects Coordinated Adolescent Growth Plate Ossification From Disruptive Physiological Mechanical Forces. (20th February 2022) - Coveney, Clarissa R; Samvelyan, Hasmik J; Miotla‐Zarebska, Jadwiga; Carnegie, Josephine; Chang, Emer; Corrin, C Jonty; Coveney, Trystan; Stott, Bryony; Parisi, Ida; Duarte, Claudia; Vincent, Tonia L; Staines, Katherine A; et al.
ABSTRACT: Compared with our understanding of endochondral ossification, much less is known about the coordinated arrest of growth defined by the narrowing and fusion of the cartilaginous growth plate. Throughout the musculoskeletal system, appropriate cell and tissue responses to mechanical force delineate morphogenesis and ensure lifelong health. It remains unclear how mechanical cues are integrated into many biological programs, including those coordinating the ossification of the adolescent growth plate at the cessation of growth. Primary cilia are microtubule‐based organelles tuning a range of cell activities, including signaling cascades activated or modulated by extracellular biophysical cues. Cilia have been proposed to directly facilitate cell mechanotransduction. To explore the influence of primary cilia in the mouse adolescent limb, we conditionally targeted the ciliary gene Intraflagellar transport protein 88 ( Ift88 fl/fl ) in the juvenile and adolescent skeleton using a cartilage‐specific, inducible Cre ( AggrecanCre ER T2 Ift88 fl/fl ). Deletion of IFT88 in cartilage, which reduced ciliation in the growth plate, disrupted chondrocyte differentiation, cartilage resorption, and mineralization. These effects were largely restricted to peripheral tibial regions beneath the load‐bearing compartments of the knee. These regions were typified by an enlarged population of hypertrophic chondrocytes. Although normal patterns of hedgehog signaling were maintained, targeting IFT88 inhibited hypertrophic chondrocyte VEGF expression and downstream vascular recruitment, osteoclastic activity, and the replacement of cartilage with bone. In control mice, increases to physiological loading also impair ossification in the peripheral growth plate, mimicking the effects of IFT88 deletion. Limb immobilization inhibited changes to VEGF expression and epiphyseal morphology in Ift88 cKO mice, indicating the effects of depletion of IFT88 in the adolescent growth plate are mechano‐dependent. We propose that during this pivotal phase in adolescent skeletal maturation, ciliary IFT88 protects uniform, coordinated ossification of the growth plate from an otherwise disruptive heterogeneity of physiological mechanical forces. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).